Nowe znaleziska naparstków ze stanowiska archeologicznego przy ulicy 3 Maja w Gdańsku - przyczynek do krawiectwa gdańskiego = New discoveries of fingerstalls at archaeological site at 3 Maja Street in Gdańsk as the contribution to Gdańsk ?s tailoring - Wołyńska, Marta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper discusses a proposal of fingerstalls typology based on the differences in their form and decoration. It further shows changes visible concurrently in both historical and archaeological sources. The author isolates four internally varied types of artefacts dated to the 16th-17th centuries. The author underlines the richness of decorative motives, analyses signatures known from monuments and compares them with cachets.
Keywords: Gdańsk - archeologia; krawiectwo - historia